Prevalência de dor musculoesquelética no aspectro da saúde do agricultor familiar - Biazus, Marcelo (2016)
The work occupies much of the active life of people and therefore has implications in the health and human aging. The working process can produce health or disease. The rural worker, specifically the family farmer, is prone to different types of occupational exposure, such as the use of physical force, awkward postures, intense work routines, leading to the occurrence of diseases. The dissertation investigates the prevalence of musculoskeletal pain, in order to identify the possible causes of the development of these diseases. The study applied gathers information obtained from 150 farmers in a small town in Rio Grande do Sul state, as of instruments associated with order symptoms of musculoskeletal and pain. The inferential statistical results point to high prevalence of musculoskeletal pain associated with the labor activity carried out by farmers. The most affected body regions are in line with the literature findings, national and international, wich are, low back and shoulder pain